Trends, networks, and critical thinking in the 21st century - Andrada, Joven (Malabon City : Mutya Publishing House, Inc., 2017)
"This book is compromised of three major topics divided into seven chapters ; each chapter is meticulously presented in an extensive manner. It is an attempt to help students develop long-term critical thinking. Through this book they will be able to grasp a better understanding about trends and will push them to reexamine key assumptions, expectations, and uncertainties about the future."
Includes references.
English text.
Keywords: Humanities; Sociology; Anthropology